Self Efficacy of Prospective Mathematics Teacher on Numerical Literacy Based on Lesson Study - Mu'jizatin Fadiana; Afifaftun Nikmah; Abdul Hasan (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2023)
One of the instruments used in National Assessment is Minimum Competency Assessment. In this assessment, there are two types of competencies that are measured, they are reading literacy and numeracy literacy. In the process of developing numeracy literacy skills for students, one of the determining factors is the teacher. The purpose of this study was to describe the self-efficacy of prospective mathematics teacher students towards numeracy literacy in lesson study-based learning activities. This research was conducted at Mathematics Education Study Program, PGRI University of Ronggolawe in 2021/2022 academic year. The subjects in this study were 28 students who were taking Ethnomathematics courses. The instrument used is an observation sheet and a self-efficacy scale on numeracy literacy. The research method used is lesson research with lesson study which has three stages in each cycle, namely plan, do and see. The research was carried out in 3 cycles. Based on the data analysis, it was found that the students' self-efficacy towards numeracy literacy was mostly in the medium category.